ANDROGEN-RECEPTOR COUPLING INHIBITOR - OKANO YURI; KANBARA TOSHIMITSU; KAWASHIMA YOSHIHITO (1999)
PROBLEM TO BE SOLVED: To obtain the subject inhibitor giving a sure effect in use, inhibiting the coupling of androgen with its receptor, capable of treating syndromes caused by the surplus of the androgen and useful for hair cosmetics, skin cosmetics, etc., by compounding berberine as an active ingredient. SOLUTION: This androgen-receptor coupling inhibitor contains berberine or its salt as an active ingredient. Berberine hydrochloride and berberine tannate are nitrogen-containing heterocyclic compounds gathered in Japanese pharmacopeia, and the berberine is plentifully contained in Coptis japonica, Phellodendri cortex, etc., having been utilized as galenicals, and can easily and highly purely be obtained by extracting the galenicals and subsequently purifying the extract. The objective inhibitor may be compounded with an astringent, an antibacterial agent, an antibiotic, etc.